2015
DOI: 10.1111/radm.12122
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the stakes of stakeholders in research and development project management: a systems approach

Abstract: Research and development (R&D) project management involves managing multiple stakeholders with conflicting stakes. This article proposes a systems approach to capture such conflicting stakes of multiple stakeholders in controversial R&D projects. The approach is illustrated using a New Zealand case study related to the use of 1080 chemical for pest management. Initially, the problem situation was structured systemically by analysing the behaviour of the main variables and by conducting a stakeholder analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 30 publications
0
49
0
Order By: Relevance
“…Overall, they must adjust to the new circumstances [79]. Stakeholders such as consumers increasingly prefer, for example, products and services that are environmentally friendly [80,81], which forces organizations to constantly reinvent themselves, look for alternatives, new management strategies, and generalized consensus with stakeholders along the value chain [82,83].…”
Section: Environmental Dimensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, they must adjust to the new circumstances [79]. Stakeholders such as consumers increasingly prefer, for example, products and services that are environmentally friendly [80,81], which forces organizations to constantly reinvent themselves, look for alternatives, new management strategies, and generalized consensus with stakeholders along the value chain [82,83].…”
Section: Environmental Dimensionmentioning
confidence: 99%
“…Project managers must also acquire skills and appropriate strategies to manage the inevitable or unpredictable conflicts that arise from this framework of relationships [79], highlighting dialogue as a transcendental tool both to increase commitment and to resolve conflicts in project management [87,88].…”
Section: Environmental Dimensionmentioning
confidence: 99%
“…Research has suggested that the integration of multiple stakeholders in NPD‐related activities leads to better performance and higher success rates (Talke and Hultink, ; Driessen and Hillebrand, ; Su et al, ; Elias, ). Previous research on how firms identify novel ideas outside their boundaries has mostly focused on either a narrow set of innovative customers (von Hippel, ; Lettl et al, ; Bilgram et al, ) or a broad set of external sources of information (Chesbrough, ; Enkel et al, ; Gassmann et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Stakeholder theory offers a framework by which to analyze influential actors inside and outside of the firm's boundaries (Freeman, ). Although previous studies have transferred the stakeholder approach to R&D management (Elias et al, ; Elias, ), the focus remains on stakeholder methods for controversial innovations or one‐time large‐scale projects. This study investigates the integration (i.e., proactive engagement with stakeholders) of downstream market stakeholders in general NPD processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation